Early Lessons from Social Protection and Jobs Response to COVID-19 in Middle East and North Africa Countries - Kamurase, Alex; Willenborg, Emma (World Bank, Washington, DC, 2022)
Countries in the Middle East and North Africa region quickly introduced measures to limit the spread of COVID-19 following the first confirmed cases. These measures included curfews, lockdowns, and social distancing. As a result of COVID-19 induced impacts, countries in the region adopted social protection measures to mitigate the human and economic impacts of the pandemic. But most of the countries in MENA were already experiencing poor macroeconomics brought on by the decline in oil prices and by fragility, conflict, and violence. Illness and loss of income due to the pandemic (largely from informal sources) exacerbated the extreme vulnerability faced by the poor and vulnerable groups. Social protection programs, and particularly social safety nets (SSNs), can help households absorb short-term consumption risk during periods of crisis and build resilience to manage future shocks. In MENA, 21 countries and territories formally announced social protection measures to cope with the impacts of COVID-19. According to a Word Bank real-time review of social protection and jobs responses to COVID-19 (updated May 2021), measures in MENA have spanned social assistance, social insurance, and labor markets programs. Social assistance measures accounted for 59 percent of overall response, whereas social insurance and labor markets made up 23 and 18 percent, respectively. Since the World Bank launched its COVID-19 response, Social Protection and Jobs (SPJ) support to MENA countries has been fast, flexible, and adaptive. The number of Bank-supported social safety net beneficiaries increased from 2 million to 16 million in just 1.5 years of response which demonstrates that social protection systems in MENA are scalable and that country systems and programs are flexible to facilitate this scalability. Early lessons suggest the World Bank significantly contributed to addressing financing, knowledge, and delivery needs based on existing lending and policy dialogue platforms, drawing on the experience in MENA as well as global learning. But lessons also suggest that social protection policy dialogue in MENA is even more important moving forward, to help countries strengthen and boost policy reforms and to design and implement social protection programs and systems that can adequately, effectively, and efficiently target the poor and vulnerable, and be able to respond to population needs during disasters and shocks. This paper provides a documentation of the context for SPJ COVID19 response in MENA countries’, a framework for continued response and some of the early lessons learned.